A reference map of human lung MRC-5 fibroblast proteins using immobilized pH gradient-isoelectric focusing-based two-dimensional electrophoresis. - Leung, K; Wait, R; Welson, S; Yan, J; Abraham, D; Black, C; Pearson, J; Dunn, M (2001)
We report the first protein map of human adult lung MRC-5 fibroblasts using isoelectric focusing-immobilized pH gradient-based two-dimensional polyacrylamide gel electrophoresis. MRC-5 is an immortalised cell line used in a wide range of investigations. The two-dimensional gel pattern of proteins generated from any given cell system provides a fingerprint that is unique to those cells. Therefore, the establishment of a protein map for a particular cell system provides a useful reference tool as a "master map" for subsequent studies using those cells. In this map a total of 98 protein spots were identified by comparative searches of the nucleotide and protein database using peptide masses obtained by matrix-assisted laser desorption/ionization time of flight following trypsin digestion. To increase the utility of the reference map, cells were cultured in both Dulbecco's modified Eagle medium (DMEM), the standard medium, and Roswell Park Memorial Institute (RPMI)-1640. Two-dimensional gel protein patterns of MRC-5 cultures were shown to be largely unaffected by the use of RPMI compared to DMEM, respectively. In combination with the reference map, the standardised protocol described provides a tool for comparative studies involving MRC-5 cells in which nonspecific variation is minimized.